Early radiographic outcomes following deltoid ligament repair in bimalleolar equivalent ankle fractures. Issue 6 (August 2022) - Sogbein, Olawale A.; Yi, Jun; Sanders, David W.; Lawendy, Abdel-Rahman; MacLeod, Mark; Del Balso, Christopher
Abstract: Background: Indications for deltoid ligament repair in bimalleolar equivalent ankle fractures are unclear. This study compared radiographic outcomes in bimalleolar equivalent ankle fractures undergoing open reduction internal fixation (ORIF) +/− deltoid ligament repair. Methods: A retrospective review of 1024 ankle fractures was performed. Bimalleolar equivalent injuries treated with ORIF +/− deltoid ligament repair were included. Radiographic assessment was performed preoperatively, and at three months postoperatively. Results: One hundred and forty-seven ankle fractures met inclusion criteria with 46 undergoing deltoid ligament repairs. There was a significant decrease in medial clear space (1.93 ± 0.65 mm vs. 2.26 ± 0.64 mm, p = 0.01), and tibiofibular clear space (3.89 ± 1.20 mm vs. 4.87 ± 1.37 mm, p = 0.0001) at 3 months postoperative in the deltoid repair group compared to the no repair group. When syndesmotic fixation was performed, there were no differences between groups. Conclusion: Deltoid ligament repair in bimalleolar equivalent ankle fractures resulted in reduced medial clear space, and tibiofibular clear space in the early postoperative period. These differences were small and remained within established normal limits. Level of clinical evidence: Level III, retrospective cohort study.